Chemometrics-Assisted UV-Vis Spectrophotometry for Quality Control of Pharmaceuticals: A Review - Laela Hayu Nurani; Citra Ariani Edityaningrum; Irnawati Irnawati; Anggita Rosiana Putri; Anjar Windarsih; Any Guntarti; Abdul Rohman (Indonesian Journal of Chemistry, 2023)
Spectroscopic method in the UV-Vis region is considered the most molecular spectrometric method for content determination of a single component. However, a lot of pharmaceutical dosage forms comprise two or more components which lead to peak overlapping. Moreover, in the chemical stability test, active pharmaceutical ingredient (API) was also found along with the degradation products, impurities, and adulterant compounds. UV-Vis spectroscopy is one of the methods of choice for the determination or quantification of a single component in pharmaceutical preparations. The pharmaceutical products typically contain two or more APIs having chromophoric agents capable of absorbing UV-Vis beams and the absorbance values are summative from the absorption of each UV-Vis active compound according to the additive nature of Lambert-Beer law. The main problem for the simultaneous determination of API along with impurities and the degradation products in pharmaceutical preparations is the presence of overlapping peaks of UV-Vis spectra. The chemometrics-assisted spectroscopy is one of the analytical efforts to solve these problems. This review highlighted the application of chemometrics in combination with UV-Vis spectroscopy for the assay of API, impurities, adulteration issues and degradation products present in pharmaceutical dosage forms.